To calculte the derivative of a function like this, you must use the chain rule, seen here:
`dy/dz = (dy)/(du) * (du)/dz`
What this rule implies is that we will define an intermediate function, `u`, such that we can take the derivative of `y` with respect to this function and so that we can take the derivative of this function with respect to `z`. The derivative of `y` with respect to `z` will be the product of these results. Also, notice that `du` cancels out in the above product.
In our case, a convenient `u` would be as follows:
`u = 7+lnz`
We can easily find `(du)/dz`:
`(du)/(dz) = 1/z`
Now, we must first find `y` in terms of `u`:
`y = sqrtu`
Now, we must differentiate, noting that `sqrtu = u^(1/2)`:
`(dy)/(du) = 1/2*u^-(1/2) = 1/(2sqrtu)`
Now, we can solve for the overall derivative `dy/dz`:
`(dy)/(dz) = (dy)/(du)*(du)/(dz) = 1/(2sqrtu) * 1/z`
To find the result for this final expression, we must substitute `7+lnz` for `u`:
`(dy)/(dz) = 1/(2zsqrt(7+lnz))`
There is your final answer! I hope this helps!